A type of piecewise and modular energy storage topology achieved by dual carrier cross phase shift SPWM control. Issue 6 (16th August 2021) - Wang, Qingsong; Hong, Zhouliang; Deng, Fujin; Cheng, Ming; Wu, Zhi; Buja, Giuseppe
Abstract: This paper proposes a novel type of piecewise and modular energy storage topology. Compared to the modular multilevel converter (MMC), the proposed topology is not only different in structure but also in concept. Firstly, the capacitors within the submodules of MMC are all replaced by lithium batteries, which can avoid the voltage imbalance among capacitors and provide a deep connection between MMC and energy storage. What's more, the micro‐unit concept is adopted to break the whole batteries within MMC into parts for each submodule by increasing the number of submodules to an extremely high level, which turns it into a novel microelement‐based energy storage device. Due to the characteristics of the proposed topology, dual carrier cross‐phase shift sinusoidal pulse width modulation (DCCPS‐SPWM) is also proposed. With the help of DCCPS‐SPWM, the proposed topology has the advantages of simple structure, easy to control, fewer total modules with the same output level, high fault tolerance, easy to detect and locate faults. The operating modes with four energy storage units per bridge arm are well analysed and extended to the case of N units. The double‐Fourier analysis is performed on the output voltage waveform, so that the harmonics of the output voltage with DCCPS‐SPWM can be clearly understood. Finally, the feasibility of the proposed topology and its control are verified by both simulation and experimental results.